2013
DOI: 10.1002/jhet.1853
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Herbicidal Activity of 2‐Aroxy‐propanamides Containing Pyrimidine and 1,3,4‐Thiadiazole Rings

Abstract: A series of novel N‐{5‐[2‐(4,6‐dimethoxy‐pyrimidin‐2‐yloxy)‐phenyl]‐[1,3,4]thiadiazol‐2‐yl}2‐aroxy‐propanamides were designed and synthesized by the multistep reactions. 2‐(4,6‐Dimethoxy‐pyrimidin‐2‐yloxy)‐benzaldehyde (1) reacted with aminothiourea to yield 2, which undergoes ring closure to give 5‐[2‐(4,6‐dimethoxy‐pyrimidin‐2‐yloxy)‐phenyl]‐[1,3,4]thiadiazol‐2‐amine (3) in the presence of ferric chloride in refluxing ethanol. 3 reacted with 2‐aroxy‐propionyl chlorides to give the target compounds 4a, 4b, 4c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Pyrazole derivatives have great importance in the medicinal and pesticide fields [13,14,15], due to their broad range of biological activity [16,17,18]. The molecules of many modern drugs with antiphlogistic, antidiabetic, analgesic, and acaricidal activity in medicine [19] and herbicidal [20,21,22], antibacterial [23,24,25], acaricidal and insecticide [26,27] in the pesticide area contain pyrazole rings as a structural fragment. As shown in Figure 1, several pyrazole derivative products have been launched or announced, and they all contain several common structural features that are essential to their activity, including an amide bond, pyrazole and an aromatic ring attached to the carbonyl of the amide bond.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrazole derivatives have great importance in the medicinal and pesticide fields [13,14,15], due to their broad range of biological activity [16,17,18]. The molecules of many modern drugs with antiphlogistic, antidiabetic, analgesic, and acaricidal activity in medicine [19] and herbicidal [20,21,22], antibacterial [23,24,25], acaricidal and insecticide [26,27] in the pesticide area contain pyrazole rings as a structural fragment. As shown in Figure 1, several pyrazole derivative products have been launched or announced, and they all contain several common structural features that are essential to their activity, including an amide bond, pyrazole and an aromatic ring attached to the carbonyl of the amide bond.…”
Section: Introductionmentioning
confidence: 99%
“…7 Among them, thiazole, especially 1,3,4-thiadiazole derivatives, which have good cell permeability, 8 exhibited a wide range of biological activities in agriculture, 9 including antifungal, [10][11][12][13][14] antibacterial, 15,16 antiviral, 17,18 insecticidal 19,20 and herbicidal activities. 21,22 To develop new structures with unique mechanisms of action, a series of novel acetophenone derivatives containing an active moiety '1,3,4-thiadiazole thioether' was designed based on our previous work. As shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…7 Among them, thiazole, especially 1,3,4-thiadiazole derivatives, which have good cell permeability, 8 exhibited a wide range of biological activities in agriculture, 9 including antifungal, 10–14 antibacterial, 15,16 antiviral, 17,18 insecticidal 19,20 and herbicidal activities. 21,22…”
Section: Introductionmentioning
confidence: 99%
“…The literature review indicated that the pyrimidine nucleus is embedded in a large number of alkaloids, in different drugs, antibiotics, antitumor, antimicrobial, cardiovascular, antiparkinsonian agents, [3][4][5][6][7][8][9][10], and in agrochemicals, fungicides and herbicidal [10][11][12]. Pyrimidine skeleton is found in vitamins like thiamine (vitamin B1), riboflavin (vitamin B2) and folic acid (vitamin B9) [10,13].…”
Section: Introductionmentioning
confidence: 99%